Advances in plant defensins - LIAO Qian-sheng; LIN Fu-cheng; LI De-bao (浙江大学学报. 农业与生命科学版)
Plant defensins are the low molecular weight peptides, which have a broad spectrum of inhibiting the growth of plant pathogens. In this article, their biological characteristics, and production, configuration and action mechanism were reviewed. The research importance and developing trends were briefly evaluated as well.